Implementasi Dakwah Dalam Komunikasi Pembangunan - Samsul Rani (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Islamic Communication (Dakwah) is a part of the development communication. However, some of national development programs which aim to change the social notion and behavior, have not been properly appreciated by the Islamic Scholars. Absolutely not, the role of these Islamic Scholars in relation to increase the concept of communication would essentially bring positive impact to succeed the national development. The interaction of Islamic Scholars, either directly or indirectly, through the verbal and contextual communication, or even through the other media, would influence the program of national development nowadays.